2003
DOI: 10.1097/01.brs.0000103340.78418.b2
|View full text |Cite
|
Sign up to set email alerts
|

Results of Skip Laminectomy—Minimum 2-Year Follow-up Study Compared With Open-Door Laminoplasty

Abstract: Skip laminectomy was less invasive to the posterior extensor mechanism including the deep extensor muscles than open-door laminoplasty. This new procedure was effective in preventing postoperative morbidities often seen after conventional laminectomy and laminoplasty with adequate decompression of the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(113 citation statements)
references
References 20 publications
(19 reference statements)
0
112
1
Order By: Relevance
“…1). This is in remarkable contrast to previously reported results of posterior procedures, which showed a decrease of up to 60% in posterior muscles after surgery [12,13]. Although neck pain was observed in 25.8% of the ACDF patients at followup, no significant association was observed between neck pain and changes in the cross-sectional area of the posterior muscles over time.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…1). This is in remarkable contrast to previously reported results of posterior procedures, which showed a decrease of up to 60% in posterior muscles after surgery [12,13]. Although neck pain was observed in 25.8% of the ACDF patients at followup, no significant association was observed between neck pain and changes in the cross-sectional area of the posterior muscles over time.…”
Section: Discussioncontrasting
confidence: 98%
“…However, ACDF may potentially affect the posterior muscles due to a loss of motion at fused segments. Although there have been several cross-sectional studies on posterior muscles in healthy subjects [2], patients undergoing posterior surgery [12,13], and those suffering from whiplash injury [3], no study to date has examined the long-term changes in posterior muscles after ACDF.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies compared surgical approaches to determine which approach would significantly reduce the incidence or severity of axial pain ( Table 2). The results of 8 of these 13 studies [7,17,22,31,[40][41][42]44] suggested that modified laminoplasty produced less axial pain than conventional laminoplasty. Modified laminoplasty included less invasive surgery and reconstructive technique.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Only one study [30] with regard to the duration of cervical orthosis after cervical laminoplasty showed no difference between the axial pain and no axial pain group (Table 1). The duration of external immobilization, which may be related to postoperative axial pain, was significantly recorded in 3 of 12 comparative studies [17,23,40] (Table 2).…”
Section: Postoperative Managementmentioning
confidence: 99%
See 1 more Smart Citation